Dextran Sulfate Sodium (DSS)‐Induced Colitis in Mice. (4th February 2014) - Chassaing, Benoit; Aitken, Jesse D.; Malleshappa, Madhu; Vijay‐Kumar, Matam
Abstract: Inflammatory bowel diseases (IBD), mainly comprising ulcerative colitis and Crohn's Disease, are complex and multifactorial diseases with unknown etiology. For the past 20 years, to study human IBD mechanistically, a number of murine models of colitis have been developed. These models are indispensable tools to decipher underlying mechanisms of IBD pathogenesis as well as to evaluate a number of potential therapeutics. Among various chemically induced colitis models, the dextran sulfate sodium (DSS)‐induced colitis model is widely used because of its simplicity and many similarities with human ulcerative colitis. This model has both advantages and disadvantages that must be considered when employed. This protocol describes the DSS‐induced colitis model, focusing on details and factors that could affect DSS‐induced pathology. Curr. Protoc. Immunol . 104:15.25.1‐15.25.14. © 2014 by John Wiley & Sons, Inc.